Karyomorphological variations in some populations of Allium subgenus Melanocrommyum section Acanthoprason in Iran - HASSAN MASTALI; MAHBOOBEH ZARE-MEHRJERDI; MARYAM NOROUZI; JALAL REZAEI (Biodiversitas Journal of Biological Diversity, 2018)
Mastali H, Zare-Mehrjerdi M, Norouzi M, Rezaei J. 2018. Karyomorphological variations in some populations of Allium subgenus Melanocrommyum section Acanthoprason in Iran. Biodiversitas 19: 720-725. Allium is the largest genus of Amaryllidaceae comprising more than 900 species belonging to 15 subgenera. Iran is reported to be a center of diversity for subgenus Melanocrommyum. Acanthoprason is a section in this subgenus. In this paper, karyomorphological variations of nine populations of four species including Allium derderianum, A. kurdistanicum, A. minutiflorum and A. subakaka of the section Acanthoprason growing in Iran were undertaken using squash technique and 2% (w/v) aceto-orcein stain. All of the populations have the same chromosome numbers 2n = 2x = 16 with the exception in Kochka population of A. derderianum 2n = 18. In the present study, the chromosome number of A. minutiflorum and new chromosome number of A. derderianum were revealed for the first time. Chromosomal characteristics were determined using photographs complemented by cluster analysis. According to dendrogram generated by the unweighted pair-group method with arithmetic average (UPGMA) cluster analysis, nine populations studied were separated into five groups at a cut off value of 5. Karyotype analysis indicated that Allium species studied here generally have metacentric and submetacentric chromosomes and symmetric karyotypes. Results of the present study revealed the natural variation in nine populations of four species of Acantoprason section which can further serve conservation and breeding planning.